Effects of the COVID-19 pandemic on cardiovascular disease financing in Indonesia (JKN claims data analysis 2019–2020) - Nugraheni, Wahyu Pudji; Retnaningsih, Ekowati; Mubasyiroh, Rofingatul; Rachmawati, Tety (Frontiers in Public Health, 2023)
The disease burden related to non-communicable diseases is a major public health problem in Indonesia. About one-third of all deaths in Indonesia are caused by cardiovascular disease. This study describes the cost of cardiovascular disease from claims data for Advanced Referral Health Facilities at BPJS Kesehatan before and during the COVID-19 pandemic. We analyzed claims data on the National Health Insurance system managed by BPJS. The data comes from referral health facilities throughout Indonesia in 2019 and 2020. Cardiovascular service claims data by sex and age group were analyzed descriptively and with different tests between years. There was a decrease in the number of patients accessing cardiovascular services at referral health facilities for all genders, age groups, and types of main diagnoses, by around 27.8%, from 933,017 (2019) to 673,801 (2020). There was a significant decrease in total claims for all types of cardiovascular disease during the COVID-19 pandemic compared to before, especially the reduction in aneurysms and aortic dissection (40.2%) and hypertensive heart disease (39.6%). The decline also occurred in all sexes and age groups, with an average percentage decline of 31.2%. Our findings show that the reduction in the cost of cardiovascular disease claims goes hand in hand with the decrease in the number of cardiovascular patient visits. To guarantee treatment for cardiovascular disease patients during the COVID-19 pandemic, BPJS can maximize the telemedicine services that have been built. The organizer of the National Health Insurance program in Indonesia has developed a JKN mobile application that has the potential for telemedicine services guaranteed by JKN. On the other hand, BPJS needs to limit promotive and preventive budgets related to CVD so that it does not become a potential catastrophic financing.